Suspension of the Enactment of the Legislative Text Challenged for its Constitutionality Before the Supreme Federal Court - Falah Salem, Assist. Lect .Hussam Al-Din; Mansour Mahmoud Al-Helou, Prof. Dr. Munjid (Basra studies journal, 2023)
The theme of this study revolves around the mechanisms for controlling the constitutionality of laws before the Supreme Federal Court and their relationship with the suspension of the execution of the law challenged constitutionally before it, and the limits of the authority of the Iraqi constitutional judge in applying urgent interim measures as a primary means to resort to by the Supreme Federal Court to remedy the harmful effects resulting from the implementation of the challenged legislative text. In order to reach the results and recommendations that emerged from this study, it was divided into demands and branches using a methodological and analytical approach. The most important proposals were the necessity of amending the law of the Supreme Federal Court by including an explicit and direct provision allowing the suspension of the execution of the legislative text challenged constitutionally before the Supreme Federal Court, and not relying on what its internal regulations provide with regard to referral to general procedures.